Looking for Laura: public criminology and hot news - Wilson, David (Waterside Press, 2011)
Children, the Internet and the crime figures -- Serial killer thrillers -- The Chief Constable - the tale of a criminal justice professional -- Celebrity cons - Bronson, Banged up and Bad girls -- Serial killers - now you see them, now you don't -- The righteous slaughter of some shootings -- The offender profile -- Explaining 'ordinary' murder and murder investigations -- Postscript: Still looking for Laura?